Into the Job or Becoming Acquainted with an Academic Institution - Andrea Handsteiner (Forum Neue Medien in der Lehre Austria, 2016)
As new faculty begin to build an academic career, three dimensions need to be part of the introductory socialization phase: knowledge of intra-organizational structures and processes, knowledge of cultural norms and values and the realization of their role within the institution. This article portrays two practical examples for the professional onboarding and socialization of academic faculty at different career levels. A Training Passport assists all newcomers during orientation. An academic leadership course within a moderated peer learning setting guides newly appointed professors through the introductory phase. Although single ideas and instruments might not be new, the example shows that each institution of higher learning needs to carefully consider an effective method for developing and socializing academic faculty within their respective cultural and environmental conditions. 30.09.2016 | Andrea Handsteiner (Vienna)